Mimicking biochar-albedo feedback in complex Mediterranean agricultural landscapes. (13th August 2015) - Bozzi, E; Genesio, L; Toscano, P; Pieri, M; Miglietta, F
Abstract: Incorporation of charcoal produced by biomass pyrolysis (biochar) in agricultural soils is a potentially sustainable strategy for climate change mitigation. However, some side effects of large-scale biochar application need to be investigated. In particular a massive use of a low-reflecting material on large cropland areas may impact the climate via changes in surface albedo. Twelve years of MODIS-derived albedo data were analysed for three pairs of selected agricultural sites in central Italy. In each pair bright and dark coloured soil were identified, mimicking the effect of biochar application on the land surface albedo of complex agricultural landscapes. Over this period vegetation canopies never completely masked differences in background soil colour. This soil signal, expressed as an albedo difference, induced a local instantaneous radiative forcing of up to 4.7 W m −2 during periods of high solar irradiance. Biochar mitigation potential might therefore be reduced up to ∼30%. This study proves the importance of accounting for crop phenology and crop management when assessing biochar mitigation potential and provides more insights into the analysis of its environmental feedback.